C2 STEREOTACTIC ABLATIVE RADIOTHERAPY (STAR) IN PATIENTS WITH ICD AND ARRHYTHMIC STORMS. (18th May 2022) - Molon, G; Costa, A; Bonapace, S; Marinelli, A; Alongi, F; Giaj Levra, N; Sicignano, G; Cuccia, F
Abstract: Background: The current therapy of recurrent ventricular tachycardia (VT) and arrhythmic storms is the radiofrequency catheter ablation (RFCA). The first experiences of stereotaxic radioablation of arrhythmia (STAR) as an alternative in patients (pts) with defibrillator (ICD) and Arrhythmic Storms are emerging. However, a standardized method for STAR is not yet available and many issues are still under discussion. We present the preliminary results of STAR in the pts of our Center. Material and method: Pts with ICDs and Arrhythmic Storms, excluded from RFCA, were referred to STAR. Diagnostics performed were Electrophysiological study (EPS) using 3D electroanatomical mapping (3DEAM) using CardioInsightTM vest (Medtronic, Minneapolis, MN), cardio–CT scan and 18F–fluorine–2–deoxy–D–glucose positron emission tomography (18FDG – PET scan) in order to identify the target area of the ventricle. In all pts a sustained monomorphic VT was induced during EPS, and 3DEAM was used to identify the exit point of the VT (Fig. 1 ). In all cases, a 3 mm thick 4D CT scan was used (Fig. 2 ) with the aid of an abdominal thermoplastic mask. Each patient was treated with a TrueBeam Linac (Varian Medical Systems, Palo Alto, CA). The prescription of the dose from 21 to 25 Gy in a single delivery. Ethics committee approval was obtained prior to each treatment. Results: From January 2020 to March 2021, 6 patients (5 M, 1 F), mean age 78 years (58–80) were treated with STAR. The median delivered dose was 25 Gy (range 21–25 Gy). In follow–up (FU) one patient died from end–stage heart failure after 30 days. At a median FU of 13 months, STAR treatment efficacy was observed in 3/5 patients, in whom no defibrillator activation was recorded. 2/5 patients had recurrence of TV, 2 and 6 months after STAR. No severe acute toxicity was recorded after radiotherapy. Conclusions: Arrhythmic stereotaxic radioablation appears to be a safe and effective therapy in PTS with ICDs and arrhythmic storms. Completely non–invasive diagnostics and therapy make it very interesting and ambitious. Additional data is needed to improve the definition of the target zone and to standardize it in patients not eligible for RFCA.